2005
DOI: 10.1158/1535-7163.mct-04-0328
|View full text |Cite
|
Sign up to set email alerts
|

Tissue transglutaminase 2 inhibition promotes cell death and chemosensitivity in glioblastomas

Abstract: Tissue transglutaminase 2 belongs to a family of transglutaminase proteins that confers mechanical resistance from proteolysis and stabilizes proteins. Transglutaminase 2 promotes transamidation between glutamine and lysine residues with the formation of covalent linkages between proteins. Transglutaminase 2 also interacts and forms complexes with proteins important in extracellular matrix organization and cellular adhesion. We have identified the novel finding that treatment of glioblastoma cells with transgl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
81
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 33 publications
7
81
0
Order By: Relevance
“…In the current study, we showed that TGase 2 inhibition promoted sensitivity to the chemotherapeutic drug doxorubicin and that this correlated with NF-nB inactivation, indicating that TGase 2 inhibition in breast cancer cells is an effective approach to promoting chemosensitivity. This is supported by the observation that the combined use of TGase inhibitors and chemotherapeutic agents decreased the size of glioblastoma tumors by 50% compared with treatment with chemotherapeutic agents (40). Given that expressions of TGase 2 and NF-nB can be induced by chemotherapeutic agents, this raises the possibility that TGase 2 inhibition in combination with NF-nB inhibition may result in increased sensitivity to chemotherapeutic drugs and represent a potentially useful therapeutic approach to the treatment of certain cancers (25,41).…”
Section: Discussionmentioning
confidence: 90%
“…In the current study, we showed that TGase 2 inhibition promoted sensitivity to the chemotherapeutic drug doxorubicin and that this correlated with NF-nB inactivation, indicating that TGase 2 inhibition in breast cancer cells is an effective approach to promoting chemosensitivity. This is supported by the observation that the combined use of TGase inhibitors and chemotherapeutic agents decreased the size of glioblastoma tumors by 50% compared with treatment with chemotherapeutic agents (40). Given that expressions of TGase 2 and NF-nB can be induced by chemotherapeutic agents, this raises the possibility that TGase 2 inhibition in combination with NF-nB inhibition may result in increased sensitivity to chemotherapeutic drugs and represent a potentially useful therapeutic approach to the treatment of certain cancers (25,41).…”
Section: Discussionmentioning
confidence: 90%
“…To our knowledge, this is the first evidence that a transglutaminase inhibitor affects CREB phosphorylation in cancer cells. As CREB regulates the transcription of many oncogenic proteins, this mechanism may be implicated in the anti-cancer properties of TG2 inhibitors (27,43).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate whether the enzymatic activity of TG2 plays a role in regulating MMP-2 expression and function, we used KCC009, a dihydroisoxazole TG2 inhibitor (27). Treatment of ovarian cancer cells with KCC009 decreased the expression (Fig.…”
Section: Tg2 Modulates the Expression Of Mmp-2 And Other Metastasis-rmentioning
confidence: 99%
“…However, cystamine treatment of Huntington mice decreased the number and size of aggregates and delayed the neuropathological sequela [22], albeit cystamine has additional non-TG2-related effects such as caspase inhibition [31]. In contrast, TG inhibitors, including KCC009 and MDC, have pro-apoptotic effects that enhance chemosensitivity of glioblastomas [32].…”
Section: Discussionmentioning
confidence: 99%